2020
DOI: 10.1111/cas.14506
|View full text |Cite
|
Sign up to set email alerts
|

Potential dual functional roles of the Y‐linked RBMY in hepatocarcinogenesis

Abstract: Hepatocellular carcinoma (HCC) is a highly heterogeneous liver cancer with significant male biases in incidence, disease progression, and outcomes. Previous studies have suggested that genes on the Y chromosome could be expressed and exert various male‐specific functions in the oncogenic processes. In particular, the RNA‐binding motif on the Y chromosome (RBMY) gene is frequently activated in HCC and postulated to promote hepatic oncogenesis in patients and animal models. In the present study, immunohistochemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 89 publications
(248 reference statements)
0
9
0
1
Order By: Relevance
“…It was not clarified that why RBM proteins family members play a dual role in tumors. Kido et al found that the dual role of RBM proteins family genes may be related to time and space (77). They discovered that RBMY acts as a suppressor in the early stages of the tumor and shows a cancer-promoting effect in RBMX competitively inhibited the combination of the RGG motif in hnRNP A1 and the sequences flanking PKM exon 9, leading to the formation of lower PKM2 and higher PKM1 levels, which attenuated the tumorigenicity and progression of BCa.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was not clarified that why RBM proteins family members play a dual role in tumors. Kido et al found that the dual role of RBM proteins family genes may be related to time and space (77). They discovered that RBMY acts as a suppressor in the early stages of the tumor and shows a cancer-promoting effect in RBMX competitively inhibited the combination of the RGG motif in hnRNP A1 and the sequences flanking PKM exon 9, leading to the formation of lower PKM2 and higher PKM1 levels, which attenuated the tumorigenicity and progression of BCa.…”
Section: Discussionmentioning
confidence: 99%
“…Kido et al. found that the dual role of RBM proteins family genes may be related to time and space ( 77 ). They discovered that RBMY acts as a suppressor in the early stages of the tumor and shows a cancer-promoting effect in the long-term progression of tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Dual functional roles of the Y-linked RBMY have been reported in hepatocarcinogenesis in different studies [ 101 , 103 , 105 107 ]. Tsuei et al showed the expression of one to four different transcripts of RBMY including wild type and variants with N-terminal RRM deletion, C-terminal SRGY (serine–arginine–glycine–tyrosine) boxes deletion, or deletion of both domains in males with HCC and hepatoblastoma.…”
Section: Liver Cancermentioning
confidence: 99%
“…It seems that RBMY functions as a male-specific tumor suppressor at early stages of HCC development and can suppress cell proliferation and pro-oncogenic pathways. However, after surviving and adapting tumor cells in proliferative mode, RBMY acts as a proto-oncogene and induces its chronic effects to promote HCC progression [ 107 ].…”
Section: Liver Cancermentioning
confidence: 99%
“…RBMY1A1 contains a conserved domain called the SRGY motif (serine, arginine, glycine, and tyrosine) that modulated its function. RBMY1 plays a signi cant role in cardiac development, spermatogenesis, infertility, prostate cancer, and hepatocellular carcinoma (HCC) (Meyfour et al, 2017b, Chua et al, 2015, Kido et al, 2020, Jangravi et al, 2013, Dasari et al, 2001.…”
Section: Introductionmentioning
confidence: 99%